Pengaruh Parental Career-Related Behaviors terhadap Kematangan Karir Siswa SMK Informatika Fithrah Insani - Zamzam Mizan Afifah Setiawan; Sartika, Dewi; Permana, Rizka Hadian (UNISBA Press, 2024)
Abstract. Career maturity is the level of an individual's ability to control career development tasks include planning, self-preparation, recognizing potential, interests and talents (Crites, 2011). Career maturity is an important thing for teenagers. By recognizing their potential, interests and talents, teenagers will be able to decide on their career choices in the future. The success of teenagers in career development tasks can’t be separated from the role of parents. There are several types of parental attitudes towards children's career development, including support, interference, and lack of engagement, this is also called parental career-related behavior. Parental behavior has a very important relationship with teenagers' career development, including aspects of exploration and career decisions. According to Dietrich & Kracke (2009), parental career-related behavior can be in line with teenagers' progress in preparing and deciding on their careers. This research aims to determine the influence of parental career-related behavior on career maturity in adolescents. The research method used is quantitative with a causality design. The subjects of this research were 70 students in classes XI and XII of SMK Informatika FithrahInsani. The measuring instrument used is the parental career related-behavior instrument from Dietrich & Kracke (2009) which has been translated and adapted by Hartini (2020) and the Career Maturity Inventory-Revised (CMI-R) from John O. Crites & Mark L. Savickas (2011) which has been translated and adapted by Niki Yuniarti (2019). The technique used is multiple regression analysis technique. The research results show that there is no significant influence from parental career-related behavior on career maturity with an influence size of 7% (R Square = 0.70). Abstrak. Kematangan karir merupakan tingkat kemampuan individu dalam menguasai tugas perkembangan karir yang diantaranya perencanaan, persiapan diri, mengenali potensi, minat dan bakat diri (Crites, 2011). Kematangan karir merupakan suatu hal yang penting bagi remaja dengan mengenali potensi, minat dan bakat diri remaja akan dapat memutuskan pilihan karirnya kelak. Keberhasilan remaja dalam memenuhi tugas-tugas perkembangan karir tidak lepas dari peran orangtua. Terdapat beberapa jenis sikap orangtua terhadap perkembangan karir anak diantaranya mendukung, mengganggu, dan kurang terlibat, hal ini disebut juga parental career-related behavior. Perilaku orang tua sangat berhubungan penting dengan perkembangan karir remaja diantaranya dalam aspek eksplorasi dan keputusan karir. Sama halnya menurut Dietrich & Kracke (2009), parental career-related behavior dapat sejalan dengan kemajuan remaja mempersiapkan dan memutuskan karirnya. Penelitian ini bertujuan untuk mengetahui pengaruh parental career-related behavior (support, interference, lack of engagement) terhadap kematangan karir pada remaja. Metode penelitian yang digunakan yaitu kuantitatif dengan desain kausalitas. Subjek penelitian ini adalah siswa kelas XI dan XII SMK Informatika Fithrah Insani yang berjumlah 70 siswa. Alat ukur yang digunakan adalah parental career related-behavior instrument dari Dietrich & Kracke (2009) yang telah diterjemahkan dan diadaptasi oleh Hartini (2020) dan Career Maturity Inventory-Revised (CMI-R) dari John O. Crites & Mark L. Savickas (2011) yang telah diterjemahkan dan diadaptasi oleh Niki Yuniarti (2019). Teknik yang digunakan yaitu teknik analisis regresi berganda. Hasil penelitian menunjukkan bahwa tidak terdapat pengaruh yang signifikan dari parental career-related behavior terhadap kematangan karir dengan besar pengaruh 7% (R Square = 0.70).